Struktur Cerita Rakyat Jayaprana-Layonsari dan Raden Sandubaya-Lala Seruni: Sebuah Tinjauan Stukturalisme Levi-Stauss - Ratu Agung Dharmi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
This research was conducted on two different regional folklore stories, namely Balinese folklore (Jayaprana-Layonsari) and Lombok folklore (Raden Sandubaya-Lala Seruni). This study aims to determine the comparison of the two folklore structures. The theory used is the theory of Levi-Strauss Structuralism. This research data was obtained through a library method by taking data from two folklore books entitled